Eliminating Child Labour in the Digital Era, Climate Change Situation, and Sustainable Business - Sudarto, Aye; Oktiawati, Hevi; Mustofa, Muhammad Bisri (Equalita: Jurnal Studi Gender dan Anak, 2025)
Child labour is a stark manifestation of severe social and economic inequality, as well as a reflection of weak social protection systems, limited access to education, and inadequate labour regulations in many countries. Data from the International Labour Organization (ILO) indicate that over 160 million children worldwide are engaged in labour, nearly half of whom are involved in hazardous work that threatens their safety, health, and development. The digital era presents both opportunities and challenges regarding this issue. On the one hand, digital technology can be leveraged to improve access to education, skills training, and the monitoring of fair labour practices. On the other hand, digitalization also creates new forms of employment that are not yet fully regulated by law, opening opportunities for the exploitation of child labour—especially in the informal economy, e-commerce, and online-based domestic industries. Child labour remains a serious challenge amid global changes in the world of work. To respond to this issue effectively in the future, a multidisciplinary approach is needed—one that integrates education, occupational health and safety, social protection, and cross-sector partnerships. By upholding the principles of social justice and the fundamental rights of workers, the world can advance toward the total elimination of child labour in line with the 2030 Sustainable Development Agenda.